(3EYOGO GdUMaj Hjf GdJOQjH h GdJYdje (B/s - (3GdYHGSj(B;(3gTGes ((3GdbGgQI (B:s (3GdYQHj ddfTQ h GdhRjY ,s, 2005)
(3jVe gPG GdcJGH OQGSI YdejI eJNUUI JSJgOa QUO h JMdjd hGbY GdJCgjd GdCcGOjej dWdGH GdUMGaI aj YOO ef CbSGe GdUMGaI HGdLGeYGJ GdeUQjI h Pdc ef NdGd efGbTI cGaI GdLhGfH GdeQJHWI HGdYedJjf GdJYdjejI h GdJOQjHjI h eG JWQMg ef eTcdGJ h JMOjGJ JDKQ aj GYOGO UMajs
Keywords: (3GdCfJQfJs; (3GdJYdjes; (3GdUMGaIs; (3hSGFd GdGJUGds